Design Of A Miniature Axial Blower For A Portable Thermal Comfort System - Zakaria, Muhammad Syafiq (Universiti Sains Malaysia, 2022)
Frontline workers wear Personal Protective Equipment (PPE) clothes to prevent the danger of getting COVID-19 as a result of the global pandemic problems. Since there is no ventilation or cooling system to reduce the effects of the heat generated, this suit causes heat to build up within. As a result, wearing a PPE suit for a long period may cause a person to be prone to heat stroke. Thus, the aim of this project is to design a fan blower that can be part of a cooling system which can reduce the adverse effects of wearing the PPE suit. The concept to build a cooling system that can be used as a way to reduce the effect of heat generated inside the PPE suit. There are various types of cooling system concepts that can be used to reduce the negative effects when wearing a PPE suit. However, for this project, the fan blower is more focused as a cooling system because the air will not run out, has no weight and is economical. The project begins by collecting some data required for the manufacture of radial impeller such as specific speed, size of blade, depth of blade and number of blades. From this data, a model will be designed using SOLIDWORK software before being printed through a 3D printer. Next, conducting experiments on the model by using a test rig can ensure whether the objective experiment can be achieved or not. From the study made, we can upgrade the fan model to meet the desired target. Numerical solution conducted using ANSYS software aims to see if the results obtained in the experiment provide similar characteristics as in the simulation. The results of this study gave a positive result where the design produced can provide a targeted air flow rate of up to 10 cfm (0.0047194745 m^3/s) by using setup at 12V, 3600 rpm and connection using tube. The simulation results also show that the experiment is accurate because the velocity will increase when passing through a narrow space such as on a venturi tube.